Authenticity of Teachers’ Made Assessment and Its’ Contribution to Students’ English Achievement - L. G. Eka Wahyuni (Jurnal Pendidikan dan Pengajaran, 2013)
This study aimed at analyzing the authenticity of teachers’ made assessment in terms of teachers’ assessment planning and implementation; and investi-gating its’ contribution to the students’ English learning achievement. Exploratory mixed method design was employed, involving 35 vocational English teachers and 35 classes of vocational students in Buleleng Regency as the sample of the study. The data were analyzed both qualitatively as well as quantitatively. The results of study indicated that the authen-ticity of teachers’ assessment planning and its’ implementation are found sufficient. Based on the statistical analysis, the teachers’ assessment planning did not have any significant contribution. It was because it had lack of authenticity and the assessments did not really assess the intended competency. However, the assessment implementation as perceived by the teachers and the students was found significantly contributive to the students’ achieve-ment. In conclusion, these three aspects of teachers’ made assessment had simultaneously significant contribution to the students’ English achievement. Keywords: assessment authenticity, teachers’ made assessment, students’ achievement